Relationship between Age, Exercise Habits, Cigarette Smoke Duration Exposure, and Lung Vital Capacity in Passive Smokers - Saskia Oktaviani Puteri; Ratnawati Ratnawati; Nura Eky Vikawati (Faculty of Medicine, Universitas Padjadjaran, 2023)
Lung vital capacity of is different for each individual depending on personal characteristics, such as age, body mass index (BMI), and exercise habits or environmental factors, such as exposure to cigarette smoke. This study aimed to determine the relationship between personal characteristics, duration of exposure to cigarette smoke, and lung vital capacity in passive smokers in one of the areas in Indonesia. This study was a cross-sectional observational analytic study conducted during the period of August to September 2019. Data were collected through interviews and measurements using the Contec SP10BT spirometer. Participants were sampled consecutively with only women who did not smoke but had at least one family member who actively smoked and was over 20 years old participated in this study. Women were selected as the population due to the fact that the proportion of passive smokers among women is higher than men, while the age group of above 20 years old was selected with a consideration of the average age for the optimum lung capacity. The relationship between personal characteristics and a history of exposure to cigarette smoke with lung vital capacity was analyzed using Pearson and Spearman correlation test. There is a significant relationship between age, exercise habits, duration of exposure to cigarette smoke, and vital lung capacity (p=0.000; p=0.018; p=0.000) among the participants of the study. However, further research is still needed to be able to generalize this finding into a broader community.